Demonstration of CD44 gene expression in cells from fine needle aspirates of breast lesions by the polymerase chain reaction. Issue 6 (December 1995) - Bolodeoku, J; Yoshida, K; Yeomans, P; Wells, C A; Tarin, D
Abstract : Aim —To demonstrate the feasibility of studying specific gene expression in fine needle aspirates from clinical lesions. The reverse transcription/polymerase chain reaction (RT-PCR) technique was used to demonstrate CD44 gene expression in cells from diagnostic fine needle aspirates taken from patients attending the outpatient clinic for breast diseases. Methods —Polyadenylated RNA was extracted from the cells remaining in the syringe barrel after fine needle aspirate cytological diagnosis of 41 patients with breast lesions. Analysis of CD44 gene expression was performed by RT-PCR using primers flanking the site for insertion of the variant exons. The resulting products were separated on 1·2% agarose gels, transferred to nylon membranes using Southern blotting and hybridised with specific probes for standard (constitutive) and variant exons of this gene. Results —On hybridisation with the CD44 standard exon probe, the expected amplified product of approximately 482 base pairs was visualised in 22 of 41 samples examined. Further hybridisation with the "variant" exon probes (exons 7 (v2), 8 (v3), 9b (v4), 12 (v7), and 15 (v10)) on 12 of these samples showed the presence of large molecular variants in all of these samples. However, the expression pattern detected with the probes for exons 7 (v2), 8 (v3) and 9b (v4) differed among the patients. Conclusions —Expression of the standard and variant regions of the CD44 gene in cells remaining in the syringe after fine needle aspiration was demonstrated using RT-PCR. The 5′ variant exon probes seemed to show different patterns of expression among the patients. Further studies are currently being conducted to determine whether there is any correlation between expression of the various components of this gene and cytological diagnosis. Using this method, it would be possible to study the expression of other candidate marker genes in breast cancer using fine needle aspirates.